The hobbit. The battle of the five armies [videorecording (Blu-Ray)] - Jackson, Peter, 1961-; McKellen, Ian; Freeman, Martin, 1971-; Armitage, Richard, 1971-; Lilly, Evangeline, 1979-; Cumberbatch, Benedict, 1976- (Warner Home Video, 2015)
The epic conclusion to the adventures of Bilbo Baggins. The dragon Smaug rains his fiery wrath down upon the defenseless men, women, and children of Lake-town. Obsessed above all else with his reclaimed treasure, Thorin sacrifices friendship and honor to hoard it as Bilbo attempts to make him see reason.